Acceptance-Based Exposure Therapy for Body Dysmorphic Disorder: A Pilot Study. Issue 4 (July 2015) - Linde, Johanna; Rück, Christian; Bjureberg, Johan; Ivanov, Volen Z.; Djurfeldt, Diana Radu; Ramnerö, Jonas
Abstract Body dysmorphic disorder (BDD) is an often severe, chronic, and disabling disorder, and although some controlled trials of cognitive behavior therapy (CBT) have shown efficacy, the body of evidence is still limited. The condition is generally considered difficult to treat, and further research to determine the effectiveness of psychological treatments for BDD is needed. The present study is the first to evaluate an acceptance-based therapy for BDD. In total, 21 patients received a 12-week group treatment consisting of weekly sessions of psychoeducation, acceptance and defusion practice, and exposure exercises to foster acceptance of internal discomfort and to strengthen the patients' committed purposeful actions. The primary outcome was BDD symptomatology (measured on the BDD-YBOCS) assessed by a psychiatrist before and after treatment and at 6 months follow-up. The secondary outcomes were self-rated BDD symptoms, psychological flexibility, depressive symptoms, quality of life, and disability. Reductions in BDD symptomatology from pre- to posttreatment were significant and showed a large effect size, d = 1.93 (95% CI 0.82–3.04). At posttreatment, 68% of the participants showed clinically significant improvement in the primary outcome variable. Treatment gains were maintained at 6 months follow-up. The treatment also resulted in significant improvements in all secondary outcomes. The dropout rate was low; 90.5% of the participants completed treatment. This study suggests that acceptance-based exposure therapy may be an efficacious and acceptable treatment for BDD that warrants further investigation in larger controlled trials.